High-Density Lipoprotein Subspecies Defined by Presence of Apolipoprotein C-III and Incident Coronary Heart Disease in Four Cohorts. Issue 13 (27th March 2018) - Jensen, Majken K.; Aroner, Sarah A.; Mukamal, Kenneth J.; Furtado, Jeremy D.; Post, Wendy S.; Tsai, Michael Y.; Tjønneland, Anne; Polak, Joseph F.; Rimm, Eric B.; Overvad, Kim; McClelland, Robyn L.; Sacks, Frank M.
Abstract : Background: The causal role of high-density lipoprotein (HDL) cholesterol in cardioprotection has been questioned by genetic and randomized studies. Novel measures that relate to HDL function may contribute new information to the prediction of cardiovascular risk. Apolipoprotein C-III (apoC-III) is a key regulator of lipoprotein metabolism. We investigated whether subspecies of HDL defined by apoC-III are associated with coronary heart disease (CHD). Methods: We used immunoaffinity chromatography to measure the apoA-I concentrations of HDL that contains and lacks apoC-III in 2 prospective studies of adults free of CHD. In MESA (Multi-Ethnic Study of Atherosclerosis), 5657 participants (52% women, 52–72 years of age) were followed for risk of CHD from 2000 to 2002 through 2013. In a case-cohort study nested within the DCH study (Danish Diet, Cancer, and Health), 3642 participants (47% women, 51–64 years of age) were followed from 1994 to 1997 through 2010. Subsequently, we conducted a meta-analysis that combined these results with the previously published findings from 2 cohort studies that used similar laboratory methodology to measure lipoproteins, totaling 2997 incident cases. Results: ApoC-III was found on 6% to 8% of apoA-I. The 2 HDL subspecies showed opposing associations, with risk of CHD in each of the individual cohorts and in the meta-analysis ( P heterogeneity between the 2 subspecies <0.01). HDL that contains apoC-III was associated with a higher risk of CHD (pooled relative risk per standard deviation, 1.09; 95% confidence interval, 1.01–1.18), whereas HDL that lacks apoC-III was associated with lower risk (relative risk, 0.76; 95% confidence interval, 0.70–0.83). The relative risk for HDL lacking apoC-III was even more negative than the relative risk for total HDL (relative risk, 0.80; 95% confidence interval, 0.74–0.87). Conclusions: Our findings from 4 prospective studies support the hypothesis that apoC-III may mark a subfraction of HDL that is associated with higher risk of CHD. New measures reflecting HDL structure and function may provide novel insights for cardiovascular risk that extend beyond traditional plasma HDL cholesterol concentrations. Abstract : Supplemental Digital Content is available in the text.